THE ROLE OF NATIONAL VALUES IN THE SPIRITUAL AND MORAL EDUCATION OF MILITARY PERSONNEL (American Journal of Technology and Applied Sciences, 2025)
Military service includes not only physical training but also spiritual and moral education. Educating young military personnel in the spirit of patriotism, selflessness, and a sense of responsibility plays an important role in their personal and professional development. National values are one of the key criteria in this process, as they enrich the inner world of young soldiers, shape their moral character, and make them strong-willed individuals. This article highlights the role of national values in the spiritual and moral education of young military personnel.